Cesarean section trends from 1992 to 2016 in Estonia and Finland: A registry‐based study - Kaire Sildver; Piret Veerus; Katrin Lang; Heti Pisarev; Mika Gissler (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction The number of cesarean sections (CSs) has grown steadily, but the underlying factors driving this increase remain unknown. Data from Medical Birth Registries were retrieved to analyze CS trends in Estonia and Finland during the period 1992–2016. Material and methods All births in Estonia (n = 356 063) and Finland (n = 1 437 234) were included. The differences between Estonia and Finland in five‐year time periods for the total CS rate, and rates in Robson 1, 2, and 5 groups (R1, R2, R5) were analyzed by logistic regression. Total CS rates were adjusted for birthweight, parity, previous CS, gestational age, singleton pregnancy, cephalic position, induction, mother's age. R1; R2; R5 rates were adjusted for birthweight and mother's age. Results In Estonia, the proportion of CSs increased from 6.5% to 21.0% and in Finland from 15.1% to 16.8% between 1992 and 2016. In 2016, Estonia and Finland remained within the target value with their R1 + 2 (Estonia 18%; Finland 16%) and R5 (Estonia 59%; Finland 42%) values. Conclusions Comparing Robson groups in different countries can shed light on divergent CS rates and to improve the quality of perinatal and obstetric care.